Studies of fruitflies associated with mistletoe in Australia and Pakistan with notes and decriptions on genera related to Perilampsis Bezzi (Diptera: Tephritidae). - Hardy, D. Elmo (Contributions to Entomology = Beiträge zur Entomologie, 1967)
This paper treats the known species of fruitflies associated with mistletoe (Loranthaceae) in Asia and the Pacific and gives descriptive notes on related African genera. The following are described as new: Paraceratitella gen. n.? P. eurycephala sp. n., P. oblonga sp. n., Ceratitella asiatica sp. n., C. bifasciata sp. n., and C. unifasciata sp. n. Trirhithromyia Hendel is a new combination for Ceratitis (Trirhithromyia). Nomenclatural Acts asiatica Hardy, 1967 (Ceratitella), spec. n. bifasciata Hardy, 1967 (Ceratitella), spec. n. unifasciata Hardy, 1967 (Ceratitella), spec. n. eurycephala Hardy, 1967 (Paraceratitella), spec. n. oblonga Hardy, 1967 (Paraceratitella), spec. n. Paraceratitella Hardy, 1967 (Tephritidae), gen. n. Trirhithromyia (Hendel, 1931) (Tephritidae), stat. n. hitherto subgenus of Ceratitis